Jupiter's X-ray and EUV auroras monitored by Chandra, XMM-Newton, and Hisaki satellite - Kimura,T; Kraft,RP; Elsner,RF; Branduardi-Raymont,G; Gladstone,GR; Tao,C; Yoshioka,K; Murakami,G; Yamazaki,A; Tsuchiya,F; Vogt,MF; Masters,A; et al. (Journal of Geophysical Research: Space Physics, 2016)
Jupiter's X-ray auroral emission in the polar cap region results from particles which have undergone strong field-aligned acceleration into the ionosphere. The origin of precipitating ions and electrons and the time variability in the X-ray emission are essential to uncover the driving mechanism for the high-energy acceleration. The magnetospheric location of the source field line where the X-ray is generated is likely affected by the solar wind variability. However, these essential characteristics are still unknown because the long-term monitoring of the X-rays and contemporaneous solar wind variability has not been carried out. In April 2014, the first long-term multiwavelength monitoring of Jupiter's X-ray and EUV auroral emissions was made by the Chandra X-ray Observatory, XMM-Newton, and Hisaki satellite. We find that the X-ray count rates are positively correlated with the solar wind velocity and insignificantly with the dynamic pressure. Based on the magnetic field mapping model, a half of the X-ray auroral region was found to be open to the interplanetary space. The other half of the X-ray auroral source region is magnetically connected with the prenoon to postdusk sector in the outermost region of the magnetosphere, where the Kelvin-Helmholtz (KH) instability, magnetopause reconnection, and quasiperiodic particle injection potentially take place. We speculate that the high-energy auroral acceleration is associated with the KH instability and/or magnetopause reconnection. This association is expected to also occur in many other space plasma environments such as Saturn and other magnetized rotators.